Predictors of morbidity and mortality of extramural neonates with respect to TOPS score: prospective experience from a tertiary care centre of western India - Mehta, Charul R.; Singh, Diwakar K.; Verma, Aashna; Patel , Mehul (International Journal of Contemporary Pediatrics, 2023)
Background: The transport of sick newborns in India is still at a premature stage. Many of these newborns thus transported are cold, blue, and hypoglycaemic, and 75% of the babies transferred this way have serious clinical implications. The aim of this study was to study the clinical status of neonates transported to our hospital and predict the outcome in terms of morbidity and mortality, based on the TOPS score. Methods: This prospective, observational, longitudinal, simple randomized study was carried out over 12 months in the Department of Paediatrics, Civil Hospital Ahmedabad, Gujarat, and a total of 750 patients were enrolled. A detailed history and clinical examination were carried out through a preformed proforma. Results: The parameter that was found to be most altered was temperature (70.6%), 52% had hypoxia, 48.6% had poor perfusion and 20% patients had hypoglycemia. Hypoxia was the strongest predictor of mortality. 74.8% of the neonates referred to our hospital had TOPS score of 4-6, and had the highest mortality (41.3%). 25.2% of the newborns were having a TOPS score of 7-8. Conclusions: TOPS is a simple, reliable score which can help in the quick assessment of neonates on arrival. Hypothermia was the most common altered parameter at the time of presentation followed by hypoxia and hypoperfusion. Mortality was found to be statistically significant in those sick newborns, who presented with more than one altered parameter of TOPS.